Reassessing wage-led growth in Europe: Some sceptical notes - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2025)
This comment critically examines the recent claim by Alcobia and Barradas that the European Union follows a wage-led growth regime, warranting pro-labour policy intervention. While their findings support a clear policy stance, closer inspection reveals significant methodological and empirical shortcomings, including data limitations, panel heterogeneity, and questionable assumptions about causality. The paper challenges the robustness of their conclusions and questions whether functional income distribution can be effectively influenced by policy. It argues for greater theoretical caution and contextual sensitivity in policy recommendations, particularly given the unresolved ambiguities surrounding the wage- led/profit-led growth framework in diverse European economies.
Keywords: C23; D33; E12; O47; 330; Post Keynesian economics; functional income distribution; wage-led regime research